Edukasi Keuangan dan Pemasaran untuk Peternak Jangkrik: Kunci Kesuksesan UMKM - Hakim, Melati Puspita; Syaputra, Riawan; Herawati, Tuti; Sutariyono, Sutariyono; Saefullah, Aep; Adiguna, Patria; Aisha, Neila (LPPM STIE Ganesha, 2024)
This community service activity aims to enhance the knowledge of cricket farmers in financial recording and marketing strategies to help their businesses grow effectively. Conducted on May 25, 2024, this event took place at a cricket farming UMKM (Micro, Small, and Medium Enterprises) located on Jln. Benda Permai II, Pd Benda, Pamulang District, South Tangerang. The activity is a collaboration between Sekolah Tinggi Ilmu Ekonomi Ganesha (STIE GANESHA) and local farmers. The program ran from 08:00 to 12:00 WIB and aimed to apply knowledge and research findings to improve community welfare. The participating lecturers conducted research covering digital marketing, financial analysis, and human resource development. The results of this research are expected to improve production efficiency, marketing, and financial management of UMKM. The main problems faced by the farmers include limited access to bank loans and a lack of strategies to increase sales. Through this program, STIE Ganesha is committed to supporting and developing the potential of local UMKM, while also contributing positively to the welfare of the South Tangerang community.The results of this activity showed an increase in financial and marketing literacy among cricket farming UMKM owners. Jhandriansyah, a dim sum entrepreneur and cricket farmer, expressed his gratitude for the guidance provided, stating that the collaboration with STIE Ganesha greatly helped his business grow